Simulated microgravity reduces proliferation and reorganizes the cytoskeleton of human umbilical cord mesenchymal stem cells - Quynh Chi, H N; Nghia Son, H; Chinh Chung, D; Huan, L D; Hong Diem, T; Long, L T (Physiological research, 2020)
The cytoskeleton plays a key role in cellular proliferation, cell-shape maintenance and internal cellular organization. Cells are highly sensitive to changes in microgravity, which can induce alterations in the distribution of the cytoskeletal and cell proliferation. This study aimed to assess the effects of simulated microgravity (SMG) on the proliferation and expression of major cell cycle-related regulators and cytoskeletal proteins in human umbilical cord mesenchymal stem cells (hucMSCs). A WST-1 assay showed that the proliferation of SMG-exposed hucMSCs was lower than a control group. Furthermore, flow cytometry analysis demonstrated that the percentage of SMG-exposed hucMSCs in the G0/G1 phase was higher than the control group. A western blot analysis revealed there was a downregulation of cyclin A1 and A2 expression in SMG-exposed hucMSCs as well. The expression of cyclin-dependent kinase 4 (cdk4) and 6 (cdk6) were also observed to be reduced in the SMG-exposed hucMSCs. The total nuclear intensity of SMG-exposed hucMSCs was also lower than the control group. However, there were no differences in the nuclear area or nuclear-shape value of hucMSCs from the SMG and control groups. A western blot and quantitative RT-PCR analysis showed that SMG-exposed hucMSCs experienced a downregulation of bata-actin and alpha-tubulin compared to the control group. SMG generated the reorganization of microtubules and microfilaments in hucMSCs. Our study supports the idea that the downregulation of major cell cycle-related proteins and cytoskeletal proteins results in the remodeling of the cytoskeleton and the proliferation of hucMSCs.
Keywords: pupečník; Cell Cycle; kultivované buňky; Cell Differentiation; mikrofilamenta; Cytoskeleton; Umbilical Cord; Weightlessness Simulation; Microtubules; Cell Proliferation; Mesenchymal Stem Cells; Actin Cytoskeleton; cytoskelet; buněčný cyklus; mikrotubuly; Cells, Cultured; mezenchymální kmenové buňky; Humans; simulace stavu beztíže; proliferace buněk; buněčná diferenciace; lidé